ENVIRONMENTAL EDUCATION IN SOCIAL STUDIES: THE INTEGRATED EVALUATION MODEL FOR ENVIRONMENTAL EDUCATION (IEMEE) - Ossai, Juliet; Alordiah, Caroline (Jurnal Pendidikan Ilmu Sosial, 2024)
This paper introduces the Integrated Evaluation Model for Environmental Education (IEMEE), a theoretical framework designed to assess the effectiveness of environmental education initiatives within social studies. The introduction highlights the significance and history of environmental education in social studies, outlining the objectives, research questions, and study problem. The literature review discusses the concept, benefits, theoretical frameworks, and assessment methods related to environmental education. The theoretical framework section identifies key evaluation variables, justifies the selected framework, integrates relevant frameworks, and proposes the IEMEE. The discussion and implications section summarizes the primary findings of the IEMEE, examines its implications for environmental education and evaluators, suggests additional research topics, and provides recommendations for future research. This research contributes to the field of environmental education by offering a comprehensive framework for evaluating programs within social studies, supporting systematic assessment and informed decision-making for program growth and improvement.